Improvements in 4th graders' task behavior after physical activity: mediation by inhibition? - Heemskerk, Christina Hubertina Helena Maria; Roebers, Claudia M. (Frontiers in Cognition, 2024)
This study aimed to investigate if the acute effects of a physical activity (PA) break on the on-task and off-task classroom behaviour of primary school children are mediated by inhibition.Combining arousal theory and the cognitive stimulation hypothesis, we employed a 15-minute intermittent PA protocol aiming at high-intensity with cognitive demands. We were interested in the effects of PA in real-life settings and in a feasible and sustainable manner for teachers.Thus, the PA session was short and all data collection carried out in ecologically valid school and classroom environments. Fifteen 4th grade classes were randomly assigned to the experimental group (EG; eight classes, n = 120) or waitlist control group (WCG; seven classes, n = 91).Participants were observed during normal classroom lessons for 25 minutes before and after the PA break (EG) or a business-as-usual lesson (WCG) and completed the Hearts and Flowers task, a task measuring primarily inhibition, once per observation block. We analysed the effect of PA on inhibition with ANOVA and the effect on behaviour and mediation effect with logistic multilevel models. The PA break positively affected inhibition with a small effect. Active off-task classroom behaviour was higher at post-test in the WCG, but not the EG. Of practical importance, intercept-slope interactions indicated that those with higher levels of off-task behaviour at pre-test experienced greater benefits of the PA breaks. No significant mediation of the effect of PA on task-related behaviours via inhibition was found. In conclusion, a time-efficient PA break can improve inhibition and off-task classroom behaviour in primary school children. Although these effects occur concurrently, they appear to be independent of each other.